PENGARUH METODE PERMAINAN BAHASA INDONESIA TERHADAP KETERAMPILAN MENULIS PUISI BEBAS DI SEKOLAH DASAR - Sarahena, Sarahena; Mazukii, Mazukii; Halidjah, Siti (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2018)
AbstractThe  problem  in  this  research "How  is  the influence  of  the  use  of  language  game method  on  language  skills  to free poetry  writing  skills  at  Pontianak  West  Elementary School?". The  purpose of  the study to analyze how high the influence of the use of language game  methods on student learning outcomes on learning  Indonesian class V Elementary School Pontianak West.The method used is experimental method, following quasi-experimental research, experimental design of  Nonequivalent Control Group Design. Research  sample  was  chosen randomly, with lottery, obtained class V A (control class) and class V B (experiment class) SDN 54 Pontianak Barat. Data collecting tool in the form of test result learners learners.Based  on  the  average  statistical  calculation  of  post-test  result  of  experimental class  of  77,25, the  mean  of  post-test  result  of  control  class 72,20, t count  equal  to  0,5623 and  t table  (a = 5% and dk = 24 + 25 - 2 = 47) of 1.6794, means  t_arithmetic <t_table, then  Ha accepted. So, it  is  concluded  that  there  is  influence  of  the  use  of  language  game method in learning Indonesia  language  toward  the  learning  outcomes of  the  students  of  grade  V.  Keywords: Pengaruh, metode permainan, keterampilan menulis, puisi bebas.